(untitled) (Medical Forum Monthly, 2024)
Objective: To estimate the frequency and Types of Commitant Convergent squint among patients attending EYE OPD at Mardan Medical Complex Teaching Hospital Mardan. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the MMCTH Mardan from September 2016 to October 2016. Materials and Methods: Fourteen Hundred and Two Patients were examined. Thirty Nine Patients were having Strabismus which were included in this study. Results: Total numbers of patients were 39 with commitant convergent squint, in which 25 had Accommodative esotropia, 05 has infantile esotropia, 03 had Residual esotropia, and 03 had constant esotropia with amblyopia. 18 patients were male and 21 were female.29 patients needed glasses i.e squint associated with refractive error and 10 patients were refer for surgery. Conclusion: The commonest type of squint is accommodative esotropia. Infantile type follows second. Most of the commitant convergent squint cases were children under 09 years of age.